Pengaruh Financial Distress dan Audit Tenure Terhadap Integritas Laporan Keuangan Dengan Komite Audit Sebagai Variabel Pemoderasi: Studi Empiris Pada Perusahaan Sektor Consumer Non Cyclicals Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017 - 2021 - Azis, Fahmi; Annisa, Dea (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This study aims to examine whether the effect of financial distress and audit tenure with the audit committee as a moderating variable affects the integrity of financial reports in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in 2017 – 2021. The type of research being conducted is research qualitatively using purposive sampling technique, so as to produce a sample of 31 companies with a total of 155 observational data. The analytical test used is descriptive statistical analysis test, multiple regression model selection test, classic assumption test, multiple regression analysis test and hypothesis testing. The results of the study prove that financial distress, audit tenure, and audit committees simultaneously affect the integrity of financial reports. And partially financial distress has an effect on the integrity of financial statements, audit tenure has no effect on the integrity of financial statements and the audit committee has no effect on the integrity of financial statements. Audit committee moderation cannot moderate financial distress on the integrity of financial reports, and audit committee cannot moderate tenure audits on the integrity of financial reports.